Calcium zirconate flame-sprayed structures for possible electrolyte applications. Issue 10 (15th May 2022) - Conrad, Cordula; Neumann, Marc; Freiwald, Martin; Gehre, Patrick; Schimpke, Ronny; Priese, Angelika; Aneziris, Christos G.
Abstract: The usage of tubular proton-conducting solid-state electrolysis cells is a promising method for the production of hydrogen combined with energy storage possibilities. CaZrO3 is a prospective proton-conducting electrolyte material. In the present paper, planar CaZrO3 samples – manufactured by powder-based flame spraying – are characterised in detail by XRD, SEM/EDX, porosity, gas permeability, and roughness measurements. After a secondary thermal treatment, the open porosity was decreased to approx. 6 vol%. Using cylindrical graphite supports, free-standing tubular flame-sprayed (La0.8 Sr0.2 )0.98 MnO3 –CaZrO3 half-cells were generated.